Маркетингові дослідження на ринку промислових товарів - Чекаліна, Елеонора Петрівна; Чекаліна, Наталія Геннадіївна; Шутько, Людмила Борисівна (НТУ "ХПИ", 2003)
В сучасних умовах вітчизняним підприємствам потрібне впровадження маркетингових досліджень для їхньої адаптації до поточних умов. Сучасна кончепція маркетингу являє собою соціально етичний маркетинг, згідно якої адаптація умов виробництва підприємства до умов споживача дозволяє останньому підвищувати власну ефективність.

Large industrial enterprises of Ukraine, which found in conditions of plan economy, in market conditions find oneself in crisis. And wide installation of marketing research or if necessary restructure of enterprise is necessary for going out of this situation Modern conception of marketing social-ethic marketing, which determinate real solvent of consumers relatively quality of products. Therefore, for effective production enterprise needs to adopt its activity to consumer’s condition.
Keywords: маркетинг; стратегія; прогнозування; сегментація ринку